Fetal Pericardial Teratoma - Angela Desmond, MD; Gary Satou, MD; Meena Garg, MD; Suhas Kallapur, MD; Janet Horenstein, MD; Jeffrey Goldstein, MD; Glen Van Arsdell, MD; Yalda Afshar, MD, PhD (JACC: Case Reports, 2024)
A very large fetal pericardial teratoma was diagnosed at 28 weeks’ gestation, prompting urgent multidisciplinary expert consultations to weigh the risks and benefits of various prenatal invasive procedures and preterm delivery for postnatal surgical management. Ultimately, the infant was born by planned cesarean section and underwent immediate cardiopulmonary bypass and surgical resection.